Potential mechanisms underlying podophyllotoxin-induced cardiotoxicity in male rats: toxicological evidence chain (TEC) concept - Kaiyue Ma; Lu Sun; Chunxue Jia; Hongqian Kui; Jiaqi Xie; Shidan Zang; Shixin Huang; Jinfeng Que; Chuanxin Liu; Jianmei Huang (Frontiers Media S.A., 2024)
IntroductionPodophyllotoxin (PPT) is a high-content and high-activity compound extracted from the traditional Chinese medicinal plant Dysosma versipellis (DV) which exhibits various biological activities. However, its severe toxicity limits its use. In clinical settings, patients with DV poisoning often experience adverse reactions when taking large doses in a short period. The heart is an important toxic target organ, so it is necessary to conduct 24-h acute cardiac toxicity studies on PPT to understand its underlying toxicity mechanism.MethodsBased on the concept of the toxicological evidence chain (TEC), we utilized targeted metabolomic and transcriptomic analyses to reveal the mechanism of the acute cardiotoxicity of PPT. The manifestation of toxicity in Sprague-Dawley rats, including changes in weight and behavior, served as Injury Phenotype Evidence (IPE). To determine Adverse Outcomes Evidence (AOE), the hearts of the rats were evaluated through histopathological examination and by measuring myocardial enzyme and cardiac injury markers levels. Additionally, transcriptome analysis, metabolome analysis, myocardial enzymes, and cardiac injury markers were integrated to obtain Toxic Event Evidence (TEE) using correlation analysis.ResultsThe experiment showed significant epistaxis, hypokinesia, and hunched posture in PPT group rats within 24 h after exposure to 120 mg/kg PPT. It is found that PPT induced cardiac injury in rats within 24 h, as evidenced by increased serum myocardial enzyme levels, elevated concentrations of cardiac injury biomarkers, and altered cardiac cell morphology, all indicating some degree of cardiac toxicity. Transcriptome analysis revealed that primary altered metabolic pathway was arachidonic acid metabolism after PPT exposure. Cyp2e1, Aldob were positively correlated with differential metabolites, while DHA showed positive correlation with differential genes Fmo2 and Timd2, as well as with heart injury markers BNP and Mb.ConclusionThis study comprehensively evaluated cardiac toxicity of PPT and initially revealed the mechanism of PPT-induced acute cardiotoxicity, which involved oxidative stress, apoptosis, inflammatory response, and energy metabolism disorder.